The crystal structures of fourN-(4-halophenyl)-4-oxo-4H-chromene-3-carboxamides - Gomes, Ligia R. (2015)
Four N-(4-halophenyl)-4-oxo-4H-chromene-3-carboxamides (halo = F, Cl, Br and I), N-(4-fluorophenyl)-4-oxo-4H-chromene-3-carboxamide, C16H10FNO3, N-(4-chlorophenyl)-4-oxo-4H-chromene-3-carboxamide, C16H10ClNO3, N-(4-bromophenyl)-4-oxo-4H-chromene-3-carboxamide, C16H10BrNO3, N-(4-iodophenyl)-4-oxo-4H-chromene-3-carboxamide, C16H10INO3, have been structurally characterized. The molecules are essentially planar and each exhibits an anti conformation with respect to the C—N rotamer of the amide and a cis geometry with respect to the relative positions of the Carom—Carom bond of the chromone ring and the carbonyl group of the amide. The structures each exhibit an intramolecular hydrogen-bonding network comprising an N—H⋯O hydrogen bond between the amide N atom and the O atom of the carbonyl group of the pyrone ring, forming an S(6) ring, and a weak Carom—H⋯O interaction with the O atom of the carbonyl group of the amide as acceptor, which forms another S(6) ring. All four compounds have the same supramolecular structure, consisting of R 2 2(13) rings that are propagated along the a-axis direction by unit translation. There is π–π stacking involving inversion-related molecules in each structure.